(untitled) (NAU Journal of Technology and Vocational Education, 2026)
The integration of Artificial Intelligence (AI) tools in organizational operations has created new opportunities for improving administrative efficiency and job performance, particularly among secretaries who manage communication and records in public organizations. This study investigated the extent of utilization of AI-based email management tools by secretaries in public organizations in Ebonyi State for effective job performance. One research question and one null hypothesis guided the study. A descriptive survey research design was adopted. The population comprised 527 secretaries in 32 ministries in Ebonyi State, and census sampling was used. Data were collected using a structured questionnaire titled “Questionnaire on Extent of Utilization of AI-Based Email Management Tools for Effective Job Performance by Secretaries (QEUAIEMT-EJPS)”. The instrument was validated by three experts in the field of education and yielded a reliability coefficient of 0.76 using Cronbach’s alpha. Mean and standard deviation were used to answer the research question, while two-way Analysis of Variance (ANOVA) was employed to test the hypothesis at 0.05 level of significance. Findings revealed that secretaries in public organizations in Ebonyi State rarely utilize email management tools for effective job performance. The results also showed significant differences in utilization based on gender and years of job experience. The study concluded that the overall utilization of AI-based email management tools among secretaries is low and is significantly influenced by gender and experience. It was recommended, among others, that government and management of public organizations should provide regular training, evident and up-to-date ICT infrastructure, and gender-sensitive capacity-building programmes to enhance secretaries’ utilization of AI-based email management tools for improved job performance.